If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + y) + 7x + 2y = 0 (x * 5 + y * 5) + 7x + 2y = 0 (5x + 5y) + 7x + 2y = 0 Reorder the terms: 5x + 7x + 5y + 2y = 0 Combine like terms: 5x + 7x = 12x 12x + 5y + 2y = 0 Combine like terms: 5y + 2y = 7y 12x + 7y = 0 Solving 12x + 7y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. 12x + 7y + -7y = 0 + -7y Combine like terms: 7y + -7y = 0 12x + 0 = 0 + -7y 12x = 0 + -7y Remove the zero: 12x = -7y Divide each side by '12'. x = -0.5833333333y Simplifying x = -0.5833333333y
| -7y+47=9(y+7) | | 5v^2-20v-105=0 | | -12.45-(-206.30)= | | -5/-3 | | 4x^3+5x=0 | | 0=4x^2-26x+50 | | 2.25x-1+.3x+6=180 | | 4x-4/7=-24/7 | | 0.35x=-0.10 | | (x^2-7)(4x)=0 | | 12X+15Y=525 | | 2x+3(-0.16666)=-1 | | (2x-1)+(3x-32)+(2x+13)3x=360 | | 2x+2y=72cm | | 6x+3(x+2)=18 | | 7(p-3)-10=3p+9 | | an=n+5 | | 3a-3(2a+5)=13 | | 30=-y^2-13y | | 9-b/5=5-b/2 | | 2(1.5y)+3y=-1 | | (3s+2)=(14s-1) | | X^2-8(8/2)-9 | | 2t+3t=10 | | 7(p-21)-10=3p+9 | | 4y-(y-4)=-2c | | -5(4-5x)-5(x-4)=-7x+10x | | -6+5(5y-6)= | | 0.75x-0.25=3.75 | | 3p+7=2p | | 1/3/1017 | | 18x/6•x^7/3x^5 |